The Relationship Of The Role Of Parents And Learning Motivation To The Learning Outcomes Of Class Iv Students - Priambodo, Enggar Agus; Abbas, Nuraeni (Elementary School Teacher, 2021)
This study aims to examine the relationship between the role of parents on learning outcomes, examine the relationship between student learning motivation and student learning outcomes and examine the relationship between the role of parents and student learning motivation on student learning outcomes in fourth grade SD Gugus Wijaya Kusuma Semarang City. This research uses quantitative methods. The type of research used is correlation. The sample technique used is Proportional Random Sampling as many as 124 students. Collecting data using questionnaires, interviews and documentation. The data analysis technique is descriptive statistical analysis and product moment analysis. The results showed that: (1) there was a positive and significant relationship between the role of parents and learning outcomes, the value of rcount = 0.665 and included in the strong category and contributed 44, 2%; (2) there is a positive and significant relationship between student motivation and learning outcomes, the value of rcount = 0.802 and is included in the strong category and contributes 64.3%; (3) there is a positive and significant relationship between the role of parents and students' learning motivation together with learning outcomes, the value of rcount = 0.802 is included in the strong category and contributes 64.29%. The conclusion of this study is that there is a positive and significant relationship between the role of parents and learning motivation to learn together with student learning outcomes, especially in class IV SDN Gugus Wijaya Kusuma Semarang City. (3) there is a positive and significant relationship between the role of parents and students' learning motivation together with learning outcomes, the value of rcount = 0.802 is included in the strong category and contributes 64.29%. The conclusion of this study is that there is a positive and significant relationship between the role of parents and learning motivation to learn together with student learning outcomes, especially in class IV SDN Gugus Wijaya Kusuma Semarang City. (3) there is a positive and significant relationship between the role of parents and students' learning motivation together with learning outcomes, the value of rcount = 0.802 is included in the strong category and contributes 64.29%. The conclusion of this study is that there is a positive and significant relationship between the role of parents and learning motivation to learn together with student learning outcomes, especially in class IV SDN Gugus Wijaya Kusuma Semarang City.Keywords: learning motivation; learning outcomes; parent’s, role